2015
DOI: 10.1111/1468-4446.12122
|View full text |Cite
|
Sign up to set email alerts
|

Doing good when times are bad: volunteering behaviour in economic hard times

Abstract: This paper examines how the 2008-9 recession has affected volunteering behaviours in the UK. Using a large survey dataset, we assess the recession effects on both formal volunteering and informal helping behaviours. Whilst both formal volunteering and informal helping have been in decline in the UK since 2008, the size of the decline is significantly larger for informal helping than for formal volunteering. The decline is more salient in regions that experienced a higher level of unemployment during the recess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 18 publications
2
60
3
Order By: Relevance
“…His willingness to do this reflects a discourse that the young have become less altruistic. In contrast to Putnam's speculation on the impact of economic depression promoting volunteering, Lim and Laurence (2015) found that informal and formal volunteering declined after the UK 2008 recession. This was most apparent in informal volunteering, and in disadvantaged neighbourhoods with a weaker civic organizational infrastructure and lower cultural norms of trust.…”
Section: Explaining Volunteering By the Effects Of Values Circumstancontrasting
confidence: 68%
“…His willingness to do this reflects a discourse that the young have become less altruistic. In contrast to Putnam's speculation on the impact of economic depression promoting volunteering, Lim and Laurence (2015) found that informal and formal volunteering declined after the UK 2008 recession. This was most apparent in informal volunteering, and in disadvantaged neighbourhoods with a weaker civic organizational infrastructure and lower cultural norms of trust.…”
Section: Explaining Volunteering By the Effects Of Values Circumstancontrasting
confidence: 68%
“…However, we now live in different times and the current economic crisis was not as deep. We might also wonder whether citizens in European societies in the late 00s with higher standards of living and where citizens are by and large insulated-even amongst the most resource-poor groups-by the most pernicious economic consequences through various social safety nets would suffer as much as US citizens in the late 1920s (Lim and Laurence 2015). A more recent study with data from the America's Barometer showed that there was a significant decline in social trust between 2006 and 2010 and that negative evaluations of personal and national economic situations were associated with a lower level of trust (Zizumbo-Colunga et al 2010).…”
Section: Previous Researchmentioning
confidence: 99%
“…A more recent study with data from the America's Barometer showed that there was a significant decline in social trust between 2006 and 2010 and that negative evaluations of personal and national economic situations were associated with a lower level of trust (Zizumbo-Colunga et al 2010). Lim and Laurence (2015) found that volunteering declined in the current crisis in the UK and US. Hall (1999) had also suggested that the decline in trust in the UK in the early 1980s was probably linked to economic insecurity, experiences of unemployment and pessimism for the economy emerging from the 1980 to 1982 crisis.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Commentators across both sides of the Atlantic bemoan the emergence of a "Lost Generation" of youth. As citizens try to cope with the effects of negative economic conditions, attention has also been drawn to the potential social and political effects of the recession (Bermeo & Bartels, 2014;Clarke & Heath, 2014;Giugni & Grasso, 2015c;Lim & Laurence, 2015). One type of possible negative effect of economic hardship is the decline of activism and protest around "new" issues such as the environment as individuals return to bread-and-butter issues in times of economic crisis (Giugni & Grasso, 2015a).…”
Section: Introductionmentioning
confidence: 99%